PROJEK PENGUATAN PROFIL PELAJAR PANCASILA TERHADAP PENINGKATAN KARAKTER ANAK USIA DINI - Saptawati, Saptawati; Arismunandar, Arismunandar; Herman, Herman; Mustafa, Mustafa (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Early childhood is a child who ranges from 0-6 years old. Where at this age is an important phase or called the golden age which only occurs once in human life. Early age is the most appropriate time to stumify its development. Therefore, it is necessary to make efforts to stimulate children's development with approaches, strategies, methods, plans, and media used according to the needs at each stage of their development. The purpose of this study is: To find out the description of children's character abilities after the implementation of the teaching module of the Pancasila Student Profile Strengthening Project in early childhood, to find out what factors support and inhibit children's character through the implementation of the Teaching Module of the Pancasila Student Profile Strengthening Project in early childhood. This research is a descriptive qualitative research. The subjects in this study are teachers, children and parents/guardians. The results of the study showed that the character picture of children aged 4-5 years after the implementation of the P5 teaching module changed for the better. This is evidenced by the increase in character shown by children such as increasing the character of discipline, responsibility, curiosity, independence, creativity and attitude of diversity. Factors that affect the character of children aged 4-5 years through the application of the p5 teaching module, namely supporting factors that come from the treatment given, role models and the use of teacher language. Factors that hinder the improvement of the character of children aged 4-5 years are children's trust and information media that are commonly used or seen.